On Approximate -Ternary -Homomorphisms: A Fixed Point Approach - Cho YJ (Fixed Point Theory and Applications, 2011)
Using fixed point methods, we prove the stability and superstability of -ternary additive, quadratic, cubic, and quartic homomorphisms in -ternary rings for the functional equation , for each .